EMPOWERMENT OF KARANG TARUNA THROUGH DIGITALMARKETING TO INCREASE BRANDING OF FISHING POND TOURISM IN PLUMBON VILLAGE, SIDOARJO: PEMBERDAYAAN KARANG TARUNA MELALUI DIGITAL MARKETING UNTUK MENINGKATKAN BRANDING WISATA KOLAM PANCING DESA PLUMBON, SIDOARJO - Amillia Kartika Sari; Amrina Rosyada AJ; Makhrus Minas Suhudi; Brayen Najoan; Navila Azka Salsabilla; Intan Mordova; Dinda Nuraini Fadilah; Inas Al Azizu; dita ruspitasari; nataniela safainsaurel; Muhammad Syiva Abdillah; aldila deselma mubarrokah (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Digital tourism marketing is an effort to promote and market an area or tourist attraction using digital media. Sidoarjo regency is one of the regencies in east java that has potential villages to become tourist villages, which is Plumbon Village. However, the potential and natural resources that support it to be developed are less than optimal in terms of tourism branding due to the lack of knowledge about digital marketing so that reach of the tourism is still low. This activity is in accordance with SDGs point 4 and 8 namely Quality Education and Decent Work and economic growth. Objective: The activities of this Village Community Empowerment Program are (1) increasing the knowledge of Karang Taruna Cahaya Muda members regarding digital marketing (2) providing a forum for Karang Taruna Cahaya Muda members to develop village potential through various digital marketing platforms (3) provide various trainings on digital marketing to improve the skills of Karang Taruna members. Methode: This activity uses counseling and training methods regarding digital marketing. The location of the activity is in Plumbon Village, Porong, Sidoarjo. The participants of the activity are members of the young light cadet reef. Evaluation of activities is carried out using the post-test method and focus group discussion to evaluate the results of training. Result: There is an increase in knowledge about digital marketing. Counseling participants managed to obtain an average post-test score of 70.0 from the previous only 20.0. Then, with intensive training in website and social media management, content creation, and design, it succeeded in increasing the skills of participants to 75.0 from previously only 15.0. In addition, an increase also occurred in the number of online visitors (website and social media visitors) and offline visitors. Counseling and training participants including members of Karang Taruna Cahaya Muda are expected to continue to actively manage the digital marketing platform that has been created for branding fishing pond tours. Conclusion: This activity received positive support from the village head and members of the cadet reef who participated in the counseling and training showed high enthusiasm. Through this program, cadet coral members are able to increase their knowledge and skills regarding digital marketing to branding BUMDES PONTRAS in regional and national coverage. Keyword: digital marketing, quality education, decent work and economic growth counselling, training, tourism village